2020
DOI: 10.1159/000509312
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Stereotactic Frame Registration Using a Three-Dimensional Imaging System with and without Preoperative Computed Tomography for Image Fusion

Abstract: Background: The O-arm O2 imaging system (OAO2) is an intraoperative cone beam 3D tomogram imaging tool with a wide enough field of view to perform intraoperative fiducial registration with standard stereotactic frames. However, the OAO2 3D images (cone beam CT) provide limited tissue contrast, which may reduce the accuracy of fusion to a preoperative targeting MRI for planning awake deep brain stimulation (DBS) surgeries. Therefore, most users obtain a preoperative CT scan to use as the reference exam for comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The intraoperative 3D fluoroscopic imaging system has been deemed particularly useful for verifying the position of implanted leads [6]. One major advantage of this system includes its lower radiation exposure, with an effective dose of up to 0.7 mSv being substantially two- or three-fold lower than the conventional head CT scans [10]. The employment of CBCT as a substitute for additional preoperative imaging scans for frame registration could certainly reduce extraneous burdens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The intraoperative 3D fluoroscopic imaging system has been deemed particularly useful for verifying the position of implanted leads [6]. One major advantage of this system includes its lower radiation exposure, with an effective dose of up to 0.7 mSv being substantially two- or three-fold lower than the conventional head CT scans [10]. The employment of CBCT as a substitute for additional preoperative imaging scans for frame registration could certainly reduce extraneous burdens.…”
Section: Discussionmentioning
confidence: 99%
“…While earlier research reported CBCT and conventional CT discrepancies of less than 1 mm [14, 15], the resultant electrode positioning using CBCT-based frame registration was often reported to be more imprecise (summarized in Table 3) [79]. One study noted significant alignment errors in nearly half of cases, predominantly along the z -axis [10]. We experienced similar z -axis errors in our early cases, which is likely attributed to the O-arm’s 15-cm vertical scanning limits, which can be addressed by adjusting the center position and preparing consistent patient neck position across different scan sessions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to medical imaging equipment, fusion technology can be classified as homologous image fusion and heterologous image fusion [16,17].…”
Section: Introductionmentioning
confidence: 99%